Measuring bridging forces in protein–DNA condensates - Vikhyaat Ahlawat; Hashini Ekanayake Mudiyanselage; Divya Kota; Huan-Xiang Zhou (Proceedings of the National Academy of Sciences, 2026)
Protein-DNA condensates mediate transcription and regulate gene expression and DNA replication and repair. Intermolecular bridging forces stabilizing condensates have direct roles in these processes. Here, we use optical tweezers to measure bridging forces. In the presence of protamine, a single condensate is observed on a 20.5-knt single-stranded DNA (ssDNA). Stretching produces force curves with a sawtooth pattern, suggesting condensate disassembly via sequential rupture of individual protamine–ssDNA bridges. The bridging forces are 11.3 ± 4.6 pN, with unfolding lengths of 1.3 ± 0.8 µm per bridge. In contrast, double-stranded DNA (dsDNA) forms protamine-mediated tangles that can withstand strand-separation forces (~60 pN). ssDNA tracks unpeeled at nicks on dsDNA by overstretching seed tangle formation upon retraction, but the initial condensates have a sufficient ssDNA-to-dsDNA ratio to appear liquid-like, as indicated by a sawtooth pattern in subsequent stretching. The presence of dsDNA raises bridging forces to 34 ± 8 pN, which revert to ~10 pN upon adding external ssDNA. In line with these single-molecule results, protamine–dsDNA mixtures form solid-like aggregates and require ssDNA addition to become liquid droplets. Conversely, adding dsDNA slows the fusion of protamine–ssDNA droplets. This work reports systematic characterization of bridging forces and shows that the ssDNA-to-dsDNA ratio can tune their magnitude in protein-DNA condensates.